Medicinal chemistry of bioactive natural products (Wiley-Science, 2006)
Medicinal Chemistry of Bioactive Natural Products provides a much-needed survey of bioactive natural products and their applications in medicinal chemistry. This comprehensive reference features articles by some of the world's leading scientists in the field on discovery, structure elucidation, and elegant synthetic strategies--developed for natural products--with an emphasis on the structure activity relationship of bioactive natural products. The topics have been carefully chosen on the basis of relevance to current research and to importance as clinicially useful agents.